Relationship Between the Factors and Adoption of E-payment Services among UTHM Students - Cheong, Hao Sing; Nasuredin, Juzaimi (Research in Management of Technology and Business, 2023)
The widespread availability of the internet and the increasing digitisation of payment processes have given rise to various e-payment options, such as credit and debit cards, digital and mobile wallets, electronic currency, and contactless payment ways. However, the need for awareness, security, risk, and trust are among several issues in the adoption of e-payment services. This study aims to answer the research question, which is to identify the level of factors towards adopting E-payment services among UTHM students, to identify the level of E-payment services adoption among UTHM students, and to identify the relationship between factors and adoption of E-payment services. The Unified Theory of Acceptance Use of Technology (UTAUT) framework was used as the variable factors, which were perceived usefulness, perceived ease of use, perceived security, and trust, to measure factors towards adopting E-payment services among UTHM students. This study used an online questionnaire to collect data from respondents. 876 questionnaires were distributed to the respondents, and a total of 275 sets have been returned. Descriptive analysis, central tendencies measurement of the construct, normality test, reliability analysis, and correlation analysis was used and discussed in the quantitative findings. The researcher concluded from the findings that the variables have a significant relationship towards adopting e-payment services. The implications of theoretical and practical of this study found that UTHM students’ continuance adopts e-payment services were influenced significantly by all variables from the adoption of e-payment services with using the UTAUT model, and this study may be helpful to cashless service providers as well as entrepreneurs interested in developing e-payment application services in Malaysia.